A quantitative study of the plankton and physico-chemical conditions of the River Jumna at Allahabad in 1954-55 - Chakrabarty, R D; Roy, P; Singh, S B (Indian Journal of Fisheries, 2016)
The productivity of a river or a stream has a direct bearing upon the welfareof fish life and the role of plankton in the tropic cycle has been well recognised.Not much of work has been done on plankton production of anyof the major rivers of India, although Chacko and Ganapati (1949) andChacko et al. (1953) have contributed some information on certain aspectsof plankton of rivers Adyar and Malampuzha. Observations were thereforemade in the river Jumna at Allahabad to study the abundance, seasonalfluctuations and diurnal variation of plankton in relation to physico-chemicalconditions of water. The present paper communicates the results of thesestudies made in the years 1954-55.